INCREASING FOOT CIRCULATION WITH ELECTRICAL STIMULATION IN PATIENTS WITH DIABETES MELLITUS - Iskandar Iskandar; Ridha Dharmajaya; Yesi Ariani (Belitung Nursing Journal, 2018)
Background: Peripheral arterial disorders in diabetes mellitus is a common complication that often occurs and can develop into diabetic foot ulcers. High blood sugar levels in people with diabetes mellitus can cause increased blood viscosity resulting in thickening of the capillary membrane, where erythrocytes, platelets and leucocytes are attached to the blood vessels. Electrical stimulation by placing electrodes in the calf muscle is one of the measures to increase foot blood flow that can reduce the poor foot circulation. Objective: This study aims to determine the effect of electrical stimulation in improving blood flow of patients with diabetes mellitus. Methods: The research used pre-experimental design with one-group pretest-posttest. Sampling technique using purposive sampling as many as 62 patients with diabetes mellitus. Electrical stimulation was done by attaching electrodes to left and right calf muscles for 20 minutes, with frequency 3 times a week for 2 weeks. Before and after electrical stimulation performed foot circulation examination by ankle brachial index technique. Data were analyzed using Wilcoxon signed rank test. Results: The results showed that before the stimulation was obtained the mean ankle brachial index 0.82 mmHg and after stimulation it was 0.95 mmHg (p = 0.000). There was an effect of electrical stimulation in increasing foot blood flow. A calf muscle contraction during stimulation leads to increased leg blood flow through the addition of vascular endothelial growth factor and increased nitric oxide as a vasodilator of blood vessels. Electrical stimulation can be applied in increasing the blood flow of the foot, thus preventing the occurrence of diabetic foot ulcers. Conclusion: Stimulation is one therapy that can be done to prevent poor foot circulation of patients with diabetes mellitus.